Epidemiologic Profile of Severe Acute Respiratory Infection in Brazil During the COVID-19 Pandemic: An Epidemiological Study - Sansone, Nathália Mariana Santos; Boschiero, Matheus Negri; Marson, Fernando Augusto Lima (Frontiers in Microbiology, 2022)
Background: COVID-19 is a public health issue, and monitoring confirmed cases and deaths is an essential epidemiologic tool. Methods: We performed an epidemiological study using data from DataSUS (https://opendatasus.saude.gov.br/) from December 2019 to October 2021. We evaluated the features in Brazilian hospitalized patients due to severe acute respiratory infection (SARI) during the COVID-19 pandemic. We grouped the patients into the following categories: Influenzae virus infection (G1), other respiratory viruses’ infection (G2), other known etiologic agents (G3), SARS-CoV-2 infection (G4), and undefined etiological agent (G5). We considered the clinical evolution of the patients with SARI according to the SARI patient’s groups as the outcome. We performed the multivariate statistical analysis using logistic regression, and we adopted an Alpha error of 0.05. Results: A total of 2,740,272 patients were hospitalized due to SARI in Brazil; ]1,577,279 (68.3%) patients recovered, whereas 701,607 (30.4%) died due to SARI and 30,551 (1.3%) did not have their deaths related to SARI. A major part of the patients was grouped in G4 (1,817,098; 66.3%) and G5 (896,207; 32.7%). The other groups account for less than 1% of our sample [G1: 3,474 (0.1%); G2:16,627 (0.6%); and G3: 6,866 (0.3%)]. The deaths related to SARI were more frequent in G4 (574,887; 34.7%); however, the deaths not related to SARI were more frequent among the patients categorized into the G3 (1,339; 21.3%) and G5 (25,829; 4.1%). In the multivariate analysis, the main predictors to classify the patients in the G5 compared with G4 or G1-G4 were female sex, younger age, Black race, low educational level, rural place of residence, and the use of antiviral to treat the clinical signs. Furthermore, several features predict the risk of death by SARI, such as older age, race (Black, Indigenous, and multiracial background), low educational level, living in a flu outbreak region, need for intensive care unit, and need for mechanical ventilatory support. Conclusions: The patients’ features are unequal between the patients’ groups and can be used to determine the risk of possible underreporting in our population. Patients with a higher risk of death had a different epidemiological profile compared with patients who recovered.